Groin Pain: One Complaint, Numerous Potential Origins - Review of Literature - Miasnikiewicz, Jakub; Goleniewska, Klaudia; Kamil Ciechomski; Wiktoria Cecuła; Rypel-Bośka, Joanna; Natalia Siuta; Aleksandra Stupecka; Marcin Migiel; Izabela Brynczka (Quality in Sport, 2025)
Introduction Groin pain is a prevalent and often persistent musculoskeletal issue among athletes, particularly in disciplines requiring rapid changes of direction, kicking, and high-intensity movements. Its multifactorial origin and overlapping symptomatology pose a diagnostic and therapeutic challenge for clinicians and therapists. Proper classification, accurate assessment, and individualized management are crucial for the best outcomes and minimizing time away from sport. Aim of the Study This literature review aims to synthesize current knowledge on the diagnosis, treatment, and prevention of groin pain in athletes, based on the latest evidence and clinical guidelines. The study also highlights the role of functional assessment and neuromuscular control in both rehabilitation and injury prevention. Materials and Methods A comprehensive literature search was conducted using electronic databases (PubMed, Scopus, Web of Science) to identify relevant studies, clinical guidelines, and systematic reviews published in recent years. This paper focuses on articles addressing the Doha agreement classification system, diagnostic modalities, rehabilitation strategies, and preventive programs targeting modifiable risk factors in athletic populations. Conclusion Groin pain management requires a multidisciplinary and individualized approach. The implementation of evidence-based classification systems and preventive strategies such as adductor strengthening, core stabilization, and proper load management can significantly reduce the incidence and recurrence of groin injuries. Future research should validate functional tests and refine preventive protocols to ensure greater efficacy and applicability in sport-specific contexts.